Synergy of carbon and water use efficiencies in the Huai River Basin - Langqin Hua; Fangmin Zhang; Rui Sun; Xiaolan Yu; He Ma (Ecological Indicators, 2024)
Carbon Use Efficiency (CUE) and Water Use Efficiency (WUE) are pivotal ecological indicators. Clarifying whether they change synergistically can aid in understanding how terrestrial ecosystems adapt to climate and environmental changes. Utilizing meteorological and remote sensing data, our study assessed the spatial and temporal patterns of CUE and WUE in terrestrial ecosystems within the Huai River Basin from 2001 to 2020. Our findings revealed multi-year annual averages of 0.43 and 0.82 gC kg−1H2O for CUE and WUE, respectively. While CUE showed a significant increasing trend (P < 0.01), the increase in WUE was not significant (P > 0.05). The primary drivers behind temporal variations in these efficiencies included leaf area index (LAI), temperature, and soil moisture. In 77.96 % of the basin area, CUE and WUE exhibit synergistic changes. LAI was the predominant factor affecting both CUE and WUE, and dual-factor interactions amplify their influence. These insights enhance our understanding of regional carbon and water cycles and offer valuable guidance for the refinement of ecological conservation strategies.